Distance to the pediatric oncology center does not affect survival in children with acute lymphoblastic leukemia: a report from CYP-C. Issue 4 (21st March 2021) - Lemieux-Sarrasin, Daphné; Pelland-Marcotte, Marie-Claude; Simonyan, David; Martineau, Émilie; Desbiens, Barbara; Michon, Bruno
Abstract: Remoteness is associated with worse survival in adults with cancer. We aimed to determine whether remoteness is associated with cancer outcomes in pediatric acute lymphoblastic leukemia (ALL). Canadian children with ALL entered in the CYP-C registry were included. The predictive impact of remoteness on overall survival (OS), relapse, and treatment-related complications (infections, thrombosis, bleeding, and osteonecrosis) was estimated using multivariate regression models. We included 1383 children, of whom 277 (20.0%) lived remotely (>200 km from the pediatric oncology center). The median latency to see a pediatric oncologist was longer in children living remotely. The 5-year OS (95% CI) was similar for both groups (remote: 95.2% [93.7–96.3%] vs close: 94.1% [90.5–95.2%]). No difference was found in the relapse rate between both groups and in treatment-related complications. Remoteness did not affect survival in pediatric ALL. Further research is needed to determine which models of healthcare organization optimize cancer outcomes and patients' satisfaction.